Lacy—Zarubin Agreement of 1958: Origins of Soviet-American Science Diplomacy - R. O. Reinhardt; K. A. Nemudrov (Научный диалог, 2023)
The Agreement between the USSR and the USA on exchanges in the field of culture, technology, science and education, signed on January 27, 1958 in Washington DC by W. S. Lacy US Secretary of State Special Assistant for East-West Exchanges, and G. N. Zarubin, Ambassador Extraordinary and Plenipotentiary of the USSR to the USA is considered. The question is raised about the role of this agreement in the Soviet- American science diplomacy of the late 1950s — early 1960s. Based on a review of the biographies of senior officials who participated on the American and Soviet sides in its conclusion and implementation, the personality factor in these scientific and diplomatic processes was investigated. It is proved that their high professionalism, pragmatism and the similarity of career paths had a positive impact both on reaching mutual understanding regarding the interstate agreement being concluded, and on giving the latter an extremely specific character. Particular attention is paid to the provisions of the Lacy—Zarubin agreement, which regulated the visits of scientists and researchers, as well as academic exchanges. To assess the effectiveness of the treaty implementation in this part, the Report of the US Senate Committee on Foreign Relations dated August 20, 1959, prepared under the leadership of Senator J. Fulbright, was introduced as a source and analyzed in detail. It is noted that the clarity in determining the goals, means and ways to achieve them allowed the Lacy—Zarubin agreement to become a solid and resistant to juncture fluctuations in the conditions of the Cold War, the basis for scientific and technical cooperation between the USSR and the USA, which determined the vector of their development over the decade and a half that followed the signing of the document.